Association between uric acid to high-density lipoprotein cholesterol ratio and diabetic kidney disease in US adults - Chunmei Qin; Gang Li; Yunhua Yuan; Yi Zou (Scientific Reports)
Abstract Diabetic kidney disease (DKD) is a prevalent chronic condition, with metabolism and inflammation playing crucial roles in its pathogenesis. The uric acid to high-density lipoprotein cholesterol ratio (UHR) represents a novel index reflecting inflammatory and metabolic processes, yet its relationship with DKD remains to be elucidated. This study aimed to investigate the potential association between UHR and DKD.A cross-sectional analysis was conducted utilizing data from the National Health and Nutrition Examination Survey (NHANES, 2001–2018). Weighted multivariate logistic regression was employed to evaluate the association between UHR and DKD, while restricted cubic spline analysis was performed to detect the shape of the dose–response relationships between UHR and DKD. Subgroup analysis were performed to further examine the impact of additional covariates on the UHR-DKD relationship. The study comprised 7,138 patients with diabetes, of whom 2872 (40.24%) were diagnosed with DKD. An increase in the quartile range of UHR was associated with a progressive rise in DKD prevalence (30.51% vs. 32.75% vs. 35.59% vs. 46.72%, P < 0.001).After accounting for different confounding variables, a notable positive link was found between the UHR and DKD.When UHR was treated as a categorical variable, the quartile with the highest UHR showed a 573% increase in DKD prevalence compared to the quartile with the lowest UHR (OR 6.73, 95%CI [1.97, 23.05]). The restricted cubic spline revealed a positive linear correlation between UHR and DKD. Subgroup analyses and interaction tests revealed that age significantly influenced the UHR-DKD relationship (P < 0.05). The findings of this study suggest a significant correlation between UHR and DKD in the adult population of the United States. Nevertheless, further large-scale prospective studies are warranted to substantiate these results.